Acute periprosthetic knee infection: is there still a role for DAIR? - Di Benedetto, Paolo; Di Benedetto, Enrico Daniele; Salviato, Daniele; Beltrame, Alessandro; Gissoni, Renato; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Periprosthetic knee infection is a rare complication associated with prosthetic failure; incidence change from 0,4-2% of primary total knee replacement and 5.6% in revisions. Indications for debridment, antibiotics and implant retention (DAIR) are early acute infections or acute delayed infection. Aim of the work is to check if this technique is still a successful in early infections. Methods: We have analyzed recent literature data on DAIR and all DAIR procedures in our clinic in the last 10 years, the mean time between onset of symptoms and surgery, the mean antibiotic therapy duration and results we have obtained. We evaluate the diagnostic process and different treatments in early knee periprosthetic infections, especially the DAIR approach. Results: If correct indications are followed, DAIR has a success rate in 31-100% of the cases; if it is applied in late chronic infection the success rate is 28-62%. In our experience DAIR has an 80% success rate: in 20 patients treated with DAIR we had 4 failures. Conclusions: DAIR can be considered a successful treatment, but it depends from individual patient factors, from the microorganisms involved, from the duration of antibiotic therapy and from correct choice in timing and in execution of DAIR by the orthopedic surgeon.